2022
DOI: 10.24123/mpi.v4i2.5331
|View full text |Cite
|
Sign up to set email alerts
|

Profil Tipe dan Ketepatan Rekomendasi Apoteker pada Kasus Vignette Dispesia di Salah Satu Kabupaten di Jawa Timur Indonesia

Abstract: Dispepsia merupakan salah satu gejala yang umum dijumpai di apotek, dan oleh karena itu apoteker perlu untuk mampu memberikan rekomendasi yang tepat pada pasien dengan gejala dispepsia. Penelitian ini bertujuan untuk mendeskripsikan tipe dan ketepatan rekomendasi pada dua kasus vignette dispepsia. Penelitian ini menggunakan desain potong lintang dan 42 apoteker berpartisipasi dalam penelitian ini. Instrumen penelitian menggunakan kuesioner yang berisi: (1) karakteristik apoteker dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Consistent with this finding, two Indonesian studies examining pharmacists' recommendations in cases of dyspepsia and headache also showed that appropriate recommendations were lower in cases that needed a medical referral compared to other minor ailment cases. 37,38 Sub-optimal pharmacists' recommendations in cases requiring prompt medical referral have also been reported in other international studies. 39,40 Furthermore, pharmacists' difficulties in differentiating minor symptoms that can be self-medicated and conditions that require medical referral have been previously reported.…”
Section: The Types Reasons and Appropriateness Of The Recommendations...mentioning
confidence: 65%
“…Consistent with this finding, two Indonesian studies examining pharmacists' recommendations in cases of dyspepsia and headache also showed that appropriate recommendations were lower in cases that needed a medical referral compared to other minor ailment cases. 37,38 Sub-optimal pharmacists' recommendations in cases requiring prompt medical referral have also been reported in other international studies. 39,40 Furthermore, pharmacists' difficulties in differentiating minor symptoms that can be self-medicated and conditions that require medical referral have been previously reported.…”
Section: The Types Reasons and Appropriateness Of The Recommendations...mentioning
confidence: 65%